Complexity Analysis on the Supply Chain of Brand Enterprise Countermeasures against Imitation Threats - Abudureheman Kadeer; Mingyu Zhao; Mengzhe Li (Complexity)
This paper studies the complexity of the decision system when a brand enterprise introduces new products and makes dynamic quality decisions to cope with imitation threats caused by a counterfeit enterprise. Using game theory, nonlinear system theory, and numerical simulation, the complexity characteristics of this system and consumer utility are further discussed; moreover, delay feedback control is used to restrain chaos. The conclusions are as follows: (1) The stable scope of the brand enterprise price adjustment enlarges with the increase of the adjustment parameters of new product quality and imitation price. (2) The attraction domain of the initial decisions of the counterfeit enterprise decreases when the brand enterprise makes dynamic decisions on new product quality; a higher new product quality adjustment parameter can reduce the imitation ability of the counterfeit enterprise. (3) With the growth of the degree of substitution between new products and existing products, the quality of new products is improved, the output of existing products is reduced, and the counterfeit enterprise withdraws from the market if the degree of substitution between existing products and imitations is high. (4) The dynamic system can suppress chaos and restore stability by using the delay feedback control method. Results are of great importance for managers to make reasonable decisions when dealing with imitation threats.